Antioxidant Activity Test Of Endophyte Fungi Extract From Kayu Jawa (Lannea coromandelica (Houtt.) Merr.) Roots Using Dpph Method (2,2-Diphenyl-1-1-Picrylhydrazyl) - Tharlis Dian Syah Lubis; Ismatuz Zulfa (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Indonesia has abundant and diverse natural resources from land and sea. These biological natural resources can be explored as medicinal materials well-sourced from plants, animals, or microorganisms. Endophytic fungus is a microbial resource that grows in plant tissues that can produce compounds that have the same efficacy as the host plant. Zulfa (2016) has successfully isolated the endophytic fungi from kayu Jawa (Lannea coromandelica) roots and extracted the extracts with given code A11KA, A11KB, A12KC, A12KD, A21KK, A22KJ, AP12A, AP13L, AP21C, and AP32I. Other activities in these extracts besides antibacterial activity need to be tested. So this study was conducted to test the antioxidant activity of the extract with the DPPH method and used vitamin C positive control. Fifteen samples were obtained in this study, they are MeOH A11KA; MeOH A11KB; MeOH A12KC; MeOH A12KD; MeOH A21KK; MeOH AP12A; MeOH AP13L; MeOH AP12C; MeOH AP321; EA A11KA; EA A12KC; EA AP321; EA AP12A; EA AP13L; EA A22KJ from methanol fractions (MeOH) and ethyl acetate fraction (EA). The antioxidant activity test results showed that only six samples were potential as antioxidants. Value of AAI (Antioxidant Activity Index) EA A12KC; EA A11KA; MeOH A11KA; EA AP321; MeOH AP21C; EA A22KJ and vitamin C are 2.27 (very strong), 2.07 (very strong), 1.78 (strong), 1.19 (strong), 0.81 (medium), 0.53 (medium) and 11.67 (very strong) respectively. The result of antioxidant analysis using GC-MS showed only EA A11KA showing the presence of phenol compound, the largest phenol compound in this sample was phenol, 2,4-bis (1,1-dimethyl ethyl).